Mechanisms for supporting "Green Finance" in the world practice and in Kazakhstan - Urazgalieva, М.A.; Kalaganova, N.K.; Lygina, O.I.; Rykova, I.A. (KU Publ., 2021)
Object: To study the necessity of strengthen the role of "Green" financing in the economy of Kazakhstan, the most successful examples of financing and implementation of tools to support "Green" projects in more developed countries. Accordingly, the subject of the study is the financing of the "Green" economy in the world practice and in Kazakhstan. Methods: Abstract-logical, system analysis, comparative analysis. Findings: As a result of the study, development state of "Green" financing in Kazakhstan is assessed and the experiences of advanced countries are identified. Thus, in the course of analysis more advanced countries were identified, such as China, Korea, the United Kingdom, Canada and others, which have made some progress in the release of " Green tools implementation of electricity production from renewable sources, recycling of household waste and reduction of biodegradable landfills and formation of targeted environmental investment funds, etc. Obtained results indicate that Kazakhstan has not sufficiently addressed the aspects of economy related to sources of "Green" financing that contribute preservation of environmental quality in conditions of financial resources shortage and bringing it in line with the principles of sustainable development of the country. Also, the issue of "Green economy" is not sufficiently activated, which covers such categories as "Green" economy, "Green" credit, "Green" thinking, etc. The reached conclusions outlined in the study framework are in general nature, we simply set the task-to find out the current situation on this issue and continue to rethink the modern concepts of scientific approaches in this area. Conclusions: The development of Green finance in Kazakhstan and government support the Green incentives should be aimed at ensuring the sustainable development of the Green economy through:  creating an effective mechanism for implementing "Green" finance;  formation of management system for development of "Green" finance and its consolidation in legislative and regulatory acts.
Ахыска түріктерінің Ұлы Отан соғысына қатысуы (1941–1945 жж.)
Механизмы поддержки «зеленого» финансирования в мировой практике и в Казахстане
Keywords: «Green» economy; «Green financing»; «Green investments»; «Green projects»; «Green credit»; «Green bonds»; etc.